COUNTERPRODUCTIVE WORK BEHAVIOR IN CUSTOMER SERVICE: EXPLORING THE FACTORS INVOLVED AND THEIR IMPACT ON THE ORGANIZATION - Ricky Agusiady; Didin Saepudin; Zaenal Aripin (Journal of Jabar Economic Society Networking Forum, 2024)
Counterproductive Work Behavior (CWB) in customer service is the focus of attention in the context of human resource management and customer service strategy. This phenomenon has a significant impact on organizations, including decreased customer satisfaction, financial losses, and damage to brand reputation. However, a deep understanding of the factors that influence CWB in customer service and its impact on organizations is still limited. This research aims to explore the factors involved in CWB in customer service and their impact on organizations. In addition, this research also aims to provide better insight into how management can address CWB in customer service to improve organizational performance. The research method used in this research is qualitative. Data was collected through literature studies involving journals, articles and books related to CWB in customer service. Data analysis was carried out by identifying and analyzing the main findings related to the factors that influence CWB and its impact on the organization. The research results show that there are various factors that influence CWB in customer service, including individual, organizational and situational factors. These factors include the level of job stress, job satisfaction, work culture, incentive systems, time pressure, and conflict interactions with customers. The impact of CWB on organizations includes reduced customer satisfaction, financial loss, damage to brand reputation, disruption to operational efficiency, and damage to work culture.